Nanodosimetry of light ions in targets of different size. (July 2020) - Selva, A.; Colautti, P.; Conte, V.
Abstract: Nanodosimetry measures the frequency distribution of the number of ionizations produced by primary particles in target volumes of nanometric size. At the Legnaro National Laboratories of INFN, a large measurement campaign was carried out with the Startrack nanodosimetric counter, which showed a consistent characterization of the ionization yield produced by different primary particles when the counter is filled at the design gas pressure of 300 Pa, corresponding to a mass thickness of 2.0 μg/cm 2, i.e. about 20 nm at unit density. In order to investigate the operative limits of the Startrack counter and analyse the stochastics of the ionization yield also in targets of other sizes, new measurements were carried out at lower gas pressure. A first set of measurement was carried out with different primary ions at pressures of 200 Pa and 170 Pa, corresponding to a site size in mass per area of 1.4 μg/cm 2 and 1.1 μg/cm 2, respectively. A second set of measurements was carried out with low-energy lithium ions, varying the pressure in the range 150–300 Pa, i.e. down to a site size of 1.0 μg/cm 2 (10 nm at unit density). The measured ionization cluster-size distributions were compared with Monte Carlo simulations performed with the MC-Startrack track structure code, in order to obtain a first estimation of the decrease in detection efficiency with decreasing gas pressure. The new results and their consistency with previous measurements are presented and discussed in this paper. Highlights: New measurements were taken with the Startrack counter at different gas pressures. The new data are consistent with previous measurements and Monte Carlo simulations. Detection efficiency at each pressure was assessed by comparison with simulations. An "effective target size" of 1.2 nm can be estimated when the pressure is 200 Pa.